Inhibitory Effect on the Tyrosinase Activity and Low Cytotoxicity of Monounsaturated Long-Chain Chelating Fatty Ester - ANTONIO SERGIO C. CARVALHO; TATIANA N. PEDROSA; HERONILDES A. DANTAS FILHO; RAQUEL C. MONTENEGRO; EMERSON S. LIMA; MARNE C. DE VASCONCELLOS; ALBERDAN S. SANTOS (Anais da Academia Brasileira de Ciências)
Abstract In the present study, 5-Hydroxy-2-(Oleoyloxymethyl) -4H-pyran-4-one (KMO 3), and their chelated with Cu(II) and Fe(III) ions were synthesized to explore their inhibitory activity against tyrosinase and cytotoxicity. To this end, the structures of the obtained compounds were confirmed by ATR/FT-IR, 13C and 1H-NMR, and UV-vis techniques. The results show that chelating fatty ester presents the bands at 1567m, 1511w cm-1 attributed to the coordinated carbonyl (Cu(II)←[O=C]2), and the bands at 1540m, 1519m cm−1 which were attributed to the coordinated carbonyl (Fe(III)←[O=C]3). The inhibitory effect of chelating Oleic acid 2 (inhibition 68.3% ± 4.5) showed a factor of 19 times higher than free fatty acid (3.6% ± 3.2). IC50 Anti-tyrosinase activity of the Kojic acid 1 and KMO 3 compounds were 62.8 ± 6.6 µM and 77.6 ± 4.3 µM. The IC50 and IC90 values for tyrosinase inhibitory activity for chelating fatty ester and their complexes are values > 400 µM. Finally, the assay with the series showed no hemolytic activity (EC50> 250 μg mL-1), and not cytotoxic to B16F10, ACP-02, and human dermal fibroblast cells at 100 µM and showed no hemolytic potential at the concentration of IC50 250 µM.